Metodologias para o ensino de História aos professores sem formação acadêmica nessa disciplina: um estudo na educação de jovens e adultos em São José de Ribamar/MA - MÉLO, Darlan (2021)
Teachers teaching subjects different from their academic background is an educational reality in our country, including in Youth and Adult Education in São José de Ribamar/MA. In this municipality, there are also professors who teach history who are in this situation. Thus, the general objective of this dissertation was to analyze the answers given by teachers about teaching and methodological practice in History, in order to build an e-book with methodological suggestions on the teaching of History for the 5th stage, Elementary School of EJA. The specific objectives achieved were: to identify studies and research that address teachers who teach subjects other than their academic background; situate EJA historically; talk about theoretical and methodological elements that constitute the teaching of History; investigate specifics of the methodological practice of the teacher who teaches History at EJA, and finally, produce an e-book with methodological suggestions for History teachers of the 5th stage of Youth and Adult Education in São José de Ribamar/MA, who do not have training academic in this discipline. The research subjects were the Youth and Adult Education (EJA) teachers in São José de Ribamar/MA, who teach History without academic training in this discipline, and the data collection instruments were interviews and questionnaires. As a result of the research, it was found that the textbook emerged as the main methodological resource used, the realization of a previous approach when using methodologies such as video and music, and evaluations after using them. It was also found that the knowledge in History that the surveyed teachers had came from their school years, from reading and studying textbooks in this discipline, from exchanging information with professors in the area, and from experience with the discipline in previous years. It was observed that the professors did not discredit the teaching with the History discipline, as they sought the knowledge necessary for the teaching-learning process to be achieved in its administration. We realized then, the need for a continuing education provided by the municipal educational network of São José de Ribamar/MA to these teachers in order to reduce the difficulties listed in the questionnaires and interviews.